2022
DOI: 10.3389/fpsyg.2022.982667
|View full text |Cite
|
Sign up to set email alerts
|

Paths to positive growth in parents bereaved by drug-related death: A mixed-method study

Abstract: IntroductionDrug-related deaths (DRDs) are a major public health challenge. Losing a child to a DRD can be a very stressful life event, which places parents at risk of mental and physical health problems. However, traumatic experiences like losing a child to DRD can paradoxically also lead to positive psychological changes. A mixed-method approach was used to understand the complexity of the phenomenon of post-traumatic growth experienced by parents following a DRD.MethodBy combining data from a survey (n = 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent systematic review of 27 studies on HCW demonstrated that PTG could enhance HCWs’ coping abilities in dealing with trauma, and it can be influenced by socio-demographic and psychological factors ( 27 ). Socio-demographics, such as age, gender, marital status and educational background, are assumed to be associated with PTG across diverse cohorts ( 27 , 28 ). Working situations, including region, prior experience and work hours, are associated with the PTG of resident physicians during the COVID-19 pandemic ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of 27 studies on HCW demonstrated that PTG could enhance HCWs’ coping abilities in dealing with trauma, and it can be influenced by socio-demographic and psychological factors ( 27 ). Socio-demographics, such as age, gender, marital status and educational background, are assumed to be associated with PTG across diverse cohorts ( 27 , 28 ). Working situations, including region, prior experience and work hours, are associated with the PTG of resident physicians during the COVID-19 pandemic ( 27 ).…”
Section: Introductionmentioning
confidence: 99%